Comparative Study of Heart Rate, Blood Pressure and Selective Attention of Subjects Before and After Music - Ghimire, Nisha; Yadav, Renu; Mukhopadhyay, Soumitra (Birat Journal of Health Sciences, 2019)
Introduction: Studies have shown different views regarding the effect of music in vitals e.g Heart rate (HR), Blood pressure (BP) and atiention. The effect of preferred music with lyrics in vitals and reaction time in stroop test has not been performed in Nepalese students so, we conducted the study.Objective: To find out the change in HR, BP and reaction time in Stroop test before and after their preferred music with lyrics.Methodology Thirty male medical and paramedical students aged 25.27 ± 2.0 participated in study. The vital signs and reaction time in Stroop test before and after music was taken.Results Paired-t test was used to compare means before and after exposure to music. The means are expressed as Mean ± SD. Heart rate (HR) increased after exposure to music (66.33±9.51 Vs 67.2±8.44) (p